Clinical characteristics and distribution of paediatric hand fractures at a tertiary hospital in South China: a retrospective analysis. Issue 5 (29th October 2021) - Zhi, Xinwang; Xie, Dongming; Yang, Haiyi; Hong, Kai; Chen, Weidong; Xu, Hongwen; Canavese, Federico; Zhou, Qinghe
Abstract : The aim of this study was to evaluate the characteristics of paediatric hand fractures (PHF) at a tertiary hospital in South China based on sex, age, mechanism of injury and anatomical region. A retrospective observational study was performed on children aged 15 years and younger who were referred for actual or suspected hand fractures between January 2016 and December 2020. Medical records and radiographs were reviewed for age at the time of injury, sex, site and fracture pattern and mechanism of injury. A total of 436 consecutive children with 478 hand fractures were reviewed. Hand fractures was more common in boys (281/436; 64.4%) than in girls (155/436; 35.6%), although most fractures occurred in children aged 0–3 years (198/436; 45.4%). Distal phalanges were the most commonly injured bones (184/478; 38.5%), and the base fractures were most common (151/476; 31.7%); the fifth digit was most commonly injured (150/478; 31.3%). Crush injuries were the leading cause of fracture in children younger than 6 years of age (207/325; 63.7%), whereas punch injuries were the major cause of injury in older age groups (55/153; 35.9%); 60.1% of the fractures were managed nonsurgically. This study showed patterns of PHF in a tertiary hospital in South China. It illustrates the local variability across sex, age group, injury type and injury mechanism. Such demographic data will be valuable for optimally resourcing healthcare systems locally and help guide prevention policies.